2015
DOI: 10.1371/journal.pone.0137250
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Quality Assessment of Bizerte Lagoon (Tunisia) Using Living Foraminifera Assemblages and a Multiproxy Approach

Abstract: This study investigated the environmental quality of the Bizerte Lagoon (Tunisia) through an integrated approach that combined environmental, biogeochemical, and living benthic foraminiferal analyses. Specifically, we analyzed the physicochemical parameters of the water and sediment. The textural, mineralogical, and geochemical characteristics of the sediment, including total organic carbon, total nitrogen, simultaneously extracted metals (SEM), acid volatile sulfides (AVS), chlorophyll a, CaCO3, and changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 68 publications
2
47
0
2
Order By: Relevance
“…Siqueira et al (2006) observed the TS mean value of 6.03% in Santos estuary (São Paulo State, Brazil). Using the same TS methodology of the present study, Clemente et al (2015) recorded the mean value of 1.4% in Guanabara Bay; recorded values varying from 0.03% (IT02) to 1.73% (IT10) in Itaipu Lagoon (both in Rio de Janeiro State); and Martins et al (2016) found values of 0.04% in Bizerte Lagoon (Tunisia).…”
Section: Organic Enrichment In Surface Sediments Of Slssupporting
confidence: 55%
“…Siqueira et al (2006) observed the TS mean value of 6.03% in Santos estuary (São Paulo State, Brazil). Using the same TS methodology of the present study, Clemente et al (2015) recorded the mean value of 1.4% in Guanabara Bay; recorded values varying from 0.03% (IT02) to 1.73% (IT10) in Itaipu Lagoon (both in Rio de Janeiro State); and Martins et al (2016) found values of 0.04% in Bizerte Lagoon (Tunisia).…”
Section: Organic Enrichment In Surface Sediments Of Slssupporting
confidence: 55%
“…This work is based on the study of sediments collected in March 2013 in 10 sampling stations georeferenced with a GPS, in the Bizerte Lagoon (Tunisia, Fig. 1), the same stations studied by Martins et al (2015aMartins et al ( , 2016. This work reanalyzes some selected data obtained by these authors and new geochemical data, namely lithogenic and biogenic chemical elements.…”
Section: Methodsmentioning
confidence: 99%
“…Both analyses were performed in the fine fraction. The detailed description of the procedures applied in the sediment analyses is found in Martins et al (2015aMartins et al ( , 2016. Total organic matter (TOC) content was determined with a Leco equipment.…”
Section: Methodsmentioning
confidence: 99%
“…In pristine environments, salinity, temperature, organic matter, dissolved oxygen affects the foraminifera, but the Fernando de Noronha's port area, are susceptible to the anthropic stressors, including heavy metals and polycyclic aromatic hydrocarbons (PAHs). However, the absence of the tests could be more probably linked to the local dynamics and no preservation than to the human stressors influences (Frontalini & Coccioni, 2011;Martins et al, 2013Martins et al, , 2015aMartins et al, , 2015bMartins et al, , 2016Dijkstra et al, 2017).…”
Section: Spatial-temporal Distribution and Composition Of The Sedimentsmentioning
confidence: 99%